2022
DOI: 10.3390/horticulturae8090772
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Apple (Malus × domestica (L.) Borkh) Resistance against Apple Scab (Venturia inaequalis (Cooke) Wint.) in Hybrid Breeding Material Obtained by Gene Pyramiding

Abstract: Apple scab caused by the pathogenic fungus Venturia inaequalis causes significant damage to apples. The creation of apple-scab resistant varieties is considered an alternative to pesticide-based management. To evaluate R gene inheritance, 862 apple hybrid samples were analyzed and divided into populations depending on the resistance genes (Rvi6 and Rvi5) present in the parents’ genotypes and their combinations. The field evaluation was carried out in 2016–2018 using the international VINQUEST scab evaluation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Among the testers, Prima produced the offspring with the best response to powdery mildew and was appreciated as a good parent not only for resistance to apple scab but also for resistance or tolerance to powdery mildew. These results confirmed that resistance to apple scab and powdery mildew can be further improved by the judicious selection of parents involved in future hybridizations [ 78 , 81 , 82 ].…”
Section: Discussionsupporting
confidence: 64%
“…Among the testers, Prima produced the offspring with the best response to powdery mildew and was appreciated as a good parent not only for resistance to apple scab but also for resistance or tolerance to powdery mildew. These results confirmed that resistance to apple scab and powdery mildew can be further improved by the judicious selection of parents involved in future hybridizations [ 78 , 81 , 82 ].…”
Section: Discussionsupporting
confidence: 64%
“…In commercial orchards, especially in organic farms, and in home gardens, locally bred cultivars with resistance genes, predominantly Rvi6 , have been grown in small quantities since 2011 [ 49 , 50 ]. Moreover, intensive resistant apple breeding, including resistance provided by the Rvi5 and Rvi6 genes, has been carried out in Latvia since 1989 [ 50 , 51 , 52 ]. Although there were no isolates from the Rvi5 or Rvi6 hosts among the genotyped isolates from Latvia, the virulent pathogen could infect other genotypes without resistance genes, and such sites without scab management (greenery, home gardens), near commercial orchards or nurseries, may be the source of the diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers for scab resistance genes. Gene specific markers for Rvi6 and Rvi5 (Cheng et al, 1998;Vejl et al, 2003, respectively) are used for crosses where parents are thought to carry these genes (Zelmene et al, 2022). For elite hybrids and parent cultivars, molecular screening has started also for other scab resistance gene markers.…”
Section: Scope Of Hybridisationmentioning
confidence: 99%